Diatomaceous Biosilica: A Multifunctional Resource for Biomedicine and Sustainable Applications - Letícia Guerreiro da Trindade; Monize Bürck; Eduarda Lemos de Souza; Letícia Zanchet; Marcelo Assis; Anna Rafaela Cavalcante Braga (Ceramics, 2025)
Diatomaceous biosilica has emerged as a functional material with unique properties, driving innovations in energy storage, therapeutic systems, and environmental catalysis. This article critically reviews recent advances in using natural biosilica in lithium-ion battery anodes, emphasizing how its hierarchical morphology and high porosity contribute to ion insertion and transport efficiency. Its surface chemistry enables controlled drug release and tissue regeneration in biomedical applications. Its synergy with metal catalysts enhances pollutant degradation in photocatalytic systems, especially via surface biofunctionalization. By linking these areas, this review highlights the potential of diatom biosilica as a viable and sustainable alternative to synthetic materials, promoting technological solutions aligned with circular economy and materials engineering.